Proceedings of the 22nd International Conference on Real-Time Networks and Systems 2014
DOI: 10.1145/2659787.2659821
|View full text |Cite
|
Sign up to set email alerts
|

Schedulability Analysis for Fixed Priority Real-Time Systems with Energy-Harvesting

Abstract: International audienceThis paper introduces sufficient schedulability tests for fixed-priority pre-emptive scheduling of a real-time system under energy constraints. In this problem, energy is harvested from the ambient environment and used to replenish a storage unit or battery. The set of real-time tasks is decomposed into two different types of task depending on whether their rate of energy consumption is (i) more than or (ii) no more than the storage unit replenishment rate. We show that for this task mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…As shown in Figure 7, 31% of papers focused on energy scheduling (see, e.g., [52,59,62,65,97,107]), such as studying how to combine energy-constrained scheduling algorithms with the introduction of an energy harvesting unit; 28% of papers focused on energy harvesting methods (see, e.g., [29]), such as using reinforcement learning (RL) to automatically configure a device to maximize energy storage or minimize energy consumption as much as possible (see, e.g., [23,29,36,45]). Since the energy harvesting by EHES is affected by geographic location and the surrounding environment, the collected data are different.…”
Section: Rq2: What Are the Research Goals?mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 7, 31% of papers focused on energy scheduling (see, e.g., [52,59,62,65,97,107]), such as studying how to combine energy-constrained scheduling algorithms with the introduction of an energy harvesting unit; 28% of papers focused on energy harvesting methods (see, e.g., [29]), such as using reinforcement learning (RL) to automatically configure a device to maximize energy storage or minimize energy consumption as much as possible (see, e.g., [23,29,36,45]). Since the energy harvesting by EHES is affected by geographic location and the surrounding environment, the collected data are different.…”
Section: Rq2: What Are the Research Goals?mentioning
confidence: 99%
“…In this case, how to ensure the normal scheduling of system tasks is a signification problem. In this regard, many researchers have proposed various approaches, for example, global controller track the optimal operating point of the photovoltaic panel, state of charge management for the supercapacitor, and energy harvesting real-time task scheduling with DVFS in the embedded device [5]; the time constraints of battery-powered embedded devices are extended to energy constraints [35,58,65,105,109]; a new strategy was designed in conjunction with traditional battery-powered embedded system scheduling algorithm after considering energy attributes [62,93,97,107]. Energy consumption has always been a long-term problem for embedded systems.…”
Section: Challenge Of Energy Managementmentioning
confidence: 99%
“…In 20 14, the authors of [3] in [2] introduced suffIcient schedulability tests for the PFP ASAP algorithm when there are gaining and consuming tasks. The authors of this paper have fIrst shown when there are gaining and consuming tasks, synchronous release of all tasks is not the worst case scenario for response time analysis then they present two upper bound and one lower bound response time computation method to provide suffIcient schedulability test.…”
Section: Related Workmentioning
confidence: 99%
“…Since in small embedded systems, the stable energy is needed not a large amount of energy, we have considered the piezoelectric vibration as an energy source. According to [2] the piezoelectric vibration can provide a stable energy.…”
Section: A Energy Source Modelmentioning
confidence: 99%
See 1 more Smart Citation